CUSHING'S DISEASE, COURSE AND PROGNOSIS OF THE DISEASE - Nizamova Zulfira (Web of Journals Publishing, 2025)
Cushing's disease is a neuroendocrine disorder caused by hyperproduction of adrenocorticotropic hormone (ACTH) of pituitary genesis, which leads to secondary hyperplasia of the adrenal cortex and excessive secretion of cortisol. This article discusses the etiology and pathogenesis of the disease, differentiation of Cushing's disease from Cushing's syndrome , the main clinical manifestations, methods of laboratory and instrumental diagnostics. The article is intended for endocrinologists, neurologists, surgeons, as well as specialists in the field of internal medicine and general practice.
Keywords: Cushing 's disease, hypercorticism, ACTH, cortisol, pituitary gland, pituitary adenoma, adrenal glands, adrenal cortex hyperplasia.